2014
DOI: 10.1007/s11515-014-1289-z
|View full text |Cite
|
Sign up to set email alerts
|

Amiloride and guggulsterone suppression of esophageal cancer cell growth in vitro and in nude mouse xenografts

Abstract: Esophageal adenocarcinoma is increasing in the US and Western countries and frequent gastresophageal reflux or gastresophageal reflux disease carrying gastric acid and bile acid could contribute to esophageal adenocarcinogenesis. This study was designed to detect the expression of gastric acid-inducing gene Na + /H + exchanger-1 (NHE-1) ex vivo and then to explore targeting of NHE-1 expression or activity to control esophageal cancer cell viability in vitro and in nude mouse xenografts. The data showed that NH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 25 publications
(51 reference statements)
1
23
0
Order By: Relevance
“…Inhibiting the expression of NHE1 with shRNA or its activity with amiloride resulted in an intracellular acidification of esophageal cancer cells which decreased their viability and even induced apoptosis. The suppression of tumor xenograft formation in nude mice could also be observed (Guan et al, 2014). Interestingly, Goldman and colleagues reported that stimulation of JH-EsoAd1 EAC cells or cells of the Barrett's esophagus cell line CP-A with hydrophobic bile acid will activate NHE.…”
Section: The Role Of Nhe1 In Barrett's Esophagus and Its Progression mentioning
confidence: 95%
See 2 more Smart Citations
“…Inhibiting the expression of NHE1 with shRNA or its activity with amiloride resulted in an intracellular acidification of esophageal cancer cells which decreased their viability and even induced apoptosis. The suppression of tumor xenograft formation in nude mice could also be observed (Guan et al, 2014). Interestingly, Goldman and colleagues reported that stimulation of JH-EsoAd1 EAC cells or cells of the Barrett's esophagus cell line CP-A with hydrophobic bile acid will activate NHE.…”
Section: The Role Of Nhe1 In Barrett's Esophagus and Its Progression mentioning
confidence: 95%
“…While sharing a poor 5-year overall survival rate of about 15%, EAC and ESCC originate from different cells and also differ regarding their incidence and epidemiology (Talukdar et al, 2018). EAC is an Shallat et al, 1995;Park et al, 2015Shallat et al, 1995Khan, 2003 Fitzgerald et al, 1998;Ostrowski et al, 2007;Goldman et al, 2010;Laczko et al, 2016Goldman et al, 2011Guan et al, 2014Ariyoshi et al, 2017 NHE1 Stomach…”
Section: The Role Of Nhe1 In Barrett's Esophagus and Its Progression mentioning
confidence: 99%
See 1 more Smart Citation
“…However, there are only a few studies regarding the expression of NHE1 in human cancer samples and the clinicpathologic significance of NHE1 is also poorly explored. For instance, NHE1 has been shown to be overexpress in cervical cancer [131], hepatocellular carcinoma [132], esophageal adenocarcinomas [133], breast cancer [134] and glioblastomas [135] when compared with normal tissues. In cervical cancer, the expression of NHE1 was associated with tumour invasion and pelvic lymph node metastasis, whereas in hepatocellular carcinomas NHE1 expression was associated with increased tumour size, venous invasion and advanced tumour stage [131,132].…”
Section: Expression and Prognostic Value Of Nhesmentioning
confidence: 99%
“…Melanoma [257] x tumour growth √ chemosensitization NHEs Amiloride Gliomas [146] Breast cancer [144] Esophageal cancer [133] Hepatocellular adenocarcinoma [132] Pancreas [258] x cell migration x cell invasion x cell proliferation √ chemosensitivity √ cell death Esophageal cancer [133] x tumour growth [147] Colorectal cancer [145] Gastric cancer [259] x cell proliferation √ cell death…”
Section: Omeprazolementioning
confidence: 99%